CONTINUITIES IN THE HIV/AIDS POLICY DEBATE IN SOUTH AFRICA - Fry, Lincoln Jacob (African Journal of Infectious Diseases (AJID), 2013)
Wouters et al. (2010) critiqued the prospects of success for South Africa’s new National Strategic Plan (NSP) for HIV/AIDS; they stressed the need to mobilize people living with HIV/AIDS and their communities in order to implement the comprehensive HIV/AIDS strategy. Utilizing the South African sample from the Fourth Round of the Afrobarometer survey, this paper identifies the factors which predicted respondent selection of HIV/AIDS as an important issue for the government to address. The identification of HIV/AIDS as an important governmental problem became the study’s dependent variable. Other possible important factors were whether respondents had personal knowledge of HIV/AIDS, meaning they knew someone who died of AIDS, poverty, and their assessments of the way the government was handling the HIV/AIDS crisis. Respondent background and demographic characteristics were also included in a logistic regression analysis. The results identified three factors that predicted respondent choice of HIV/AIDS: race, especially being a Black South African, the choice of health as a governmental priority, and the rural-urban dimension. The conclusion was that HIV/AIDS, as opposed to health, should be the focus of campaigns designed to mobilize public support of comprehensive HIV/AIDS strategies in South Africa.